DIVERSE ANATOMICAL CONFIGURATION OF RECURRENT LARYNGEAL NERVE IN RELATION TO INFERIOR THYROID ARTERY, AN EXPERIENCE WITH 51 THYROIDECTOMIES - Sheikh, Nadeem Ahmed; Khattak, Shahid Farooq; Aleem, Adil; Nadeem, Kanwal (Journal of Ayub Medical College Abbottabad, 2019)
Background: Objective of the study is to elaborate the anatomical variants of recurrent laryngeal nerve in relation to inferior thyroid artery, encountered during thyroidectomy operation. It is descriptive, case series, conducted at the Department of Ear Nose & Throat, Combined Military Hospital, Abbottabad. The study was conducted from January 2016 to September 2017. Methods: Fifty-one patients underwent extra-capsular thyroidectomy in general anaesthesia. The dissection was carried out in a standard way in all patients. Recurrent laryngeal nerves were identified and exposed in every patient, and their anatomical relations were recorded in database. Results: Recurrent laryngeal nerve was seen over riding the ramification of inferior thyroid artery in majority of left sided dissected specimen, however on the right side the principal nerve was found to be ascending through the branches of inferior thyroid artery. Conclusion: Iatrogenic vocal cord paralysis has sinister implication on quality of life of the patient undergoing thyroidectomy. Anatomic variants of recurrent laryngeal nerve are well known and frequent. The disastrous outcome of inadvertent recurrent laryngeal nerve trauma can be adequately prevented by thoroughly knowing its anatomical variants, and intra-operatively identifying and exposing the principal nerves. Keywords: Thyroidectomy; recurrent laryngeal nerve; anatomy; iatrogenic; vocal cord paralysis